Effect of Feature Size on Defects, Microstructure, and Mechanical Properties of Selective Laser Melted AlSi10Mg Lattice Structure - Chengkuan Peng; Junfeng Qi; Sheng Zhou; Sanqiang Yang; Ran Tao; Heng Shao; Weining Li (Metals, 2025)
Selective laser melting lightweight lattice structures have broad application prospects in the aerospace field. Understanding the dependence of mechanical performance on feature size is crucial for structure design. This work optimized the process parameters based on large-size metal blocks (20 mm) and then fabricated submillimeter features with a size of 0.4~1.0 mm. The influence of feature size on the defects, microstructures, and mechanical properties was investigated. The results showed that the dimensional errors for all size features were above 15%. When matched with appropriate border offset, these features could be printed precisely. The densification of submillimeter features was more than 99%, demonstrating the applicability of the optimized process parameters for the fine features. The porosity and relative roughness decreased and tended to stabilize with increasing feature size. Due to having less defects, the thicker features exhibited better mechanical properties in terms of ultimate strength and elongation. After being processed with polishing treatment, the roughness was reduced below 1 μm and the tensile strength increased above 320 MPa. The elastic modulus, yield strength, and elongation were also significantly improved.